PENGARUH PENDIDIKAN KESEHATAN DENGAN METODE CERAMAH TERHADAP PENGETAHUAN SISWA MENGENAI GANGGUAN KONSENTRASI - Selvia, Dina; Nisya Aulia Septiani; Neng Diana Putri Andini; Novia Ramadhani; Riva Nurizkiah; Widyadhari; Dewi Dolifah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Learning concentration is the student's ability to focus entirely on the subject matter, leaving aside all unrelated distractions. Concentration involves focusing attention on a particular problem or object, where attention is the process of selecting stimuli from the environment. This centering is only aimed at certain objects. Therefore, it is important to have good knowledge and attitude in recognizing learning concentration disorders. Health education aims to increase students' knowledge about the definition, causes, characteristics, and ways to overcome concentration disorders, to create a conducive learning environment and optimal learning outcomes. The method used in health education is the lecture method. The supporting media for this service is in the form of leaflets, and visual media with power points. Before and after health education, participants were given pre and post-test questionnaires. The results showed that health education can be done repeatedly to get optimal concentration improvement results. Thus, it can be concluded that the health education provided can be effective in increasing students' knowledge regarding learning concentration disorders. Although only health education has been carried out once, the impact on grade 11 students at MAN 1 Sumedang has shown effective results. The conclusion of health education using this lecture method is effective in increasing knowledge about learning concentration disorders in students. Keywords: Methode, health, knowledge, concentration